2023
DOI: 10.3390/gels9030199
|View full text |Cite
|
Sign up to set email alerts
|

Simple Complexity: Incorporating Bioinspired Delivery Machinery within Self-Assembled Peptide Biogels

Abstract: Bioinspired self-assembly is a bottom-up strategy enabling biologically sophisticated nanostructured biogels that can mimic natural tissue. Self-assembling peptides (SAPs), carefully designed, form signal-rich supramolecular nanostructures that intertwine to form a hydrogel material that can be used for a range of cell and tissue engineering scaffolds. Using the tools of nature, they are a versatile framework for the supply and presentation of important biological factors. Recent developments have shown promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…The authors found that the composite hydrogel exhibited injectable characteristics and excellent hemostatic functions. Tanmay et al [ 27 ] synthesized a composite hydrogel using amino acids/peptides. The hydrogel also showed excellent injectability during the experiment, was used as a delivery vehicle for anticancer drugs, and was not affected by the external environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the composite hydrogel exhibited injectable characteristics and excellent hemostatic functions. Tanmay et al [ 27 ] synthesized a composite hydrogel using amino acids/peptides. The hydrogel also showed excellent injectability during the experiment, was used as a delivery vehicle for anticancer drugs, and was not affected by the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional biomaterials, self-assembled polypeptide hydrogels exhibit unique characteristics. First, the hydrogel can be used as a drug delivery system to deliver drugs precisely to the repair site in a sustained, metered manner [ [25] , [26] , [27] ]. Second, it can support and promote cell proliferation, differentiation, and tissue regeneration, providing favorable conditions for successful tissue engineering [ 22 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials have been used extensively as drug delivery systems to improve the treatment of a plethora of disorders (see review), [ 12 ] including the delivery of drugs targeted at activating suicide genes. Most noteworthy has been the development [ 38 ] and subsequent clinical trial [ 39 ] of the intraocular polyvinyl alcohol (PVA) and ethylene vinyl acetate (EVA) suture‐implanted device (Vitrasert®) that sustained GCV over several months, delaying the progression of cytomegalovirus retinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional to this will be the need for regulatory approval for the use of a genetically modified cell product, however the HSV-TK suicide gene has previously been used in several clinical trials of haematopoietic stem cell transplantation in leukemia within the EU and USA -see review. [37] Biomaterials have been used extensively as drug delivery systems to improve the treatment of a plethora of disorders (see review), [12] including the delivery of drugs targeted at activating suicide genes. Most noteworthy has been the development [38] and subsequent clinical trial [39] of the intraocular polyvinyl alcohol (PVA) and ethylene vinyl acetate (EVA) suture-implanted device (Vitrasert®) that sustained GCV over several months, delaying the progression of cytomegalovirus retinitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation